РІВНОМІРНЕ РОЗПОДІЛЕННЯ НАВАНТАЖЕНЬ У МЕРЕЖІ 0,38/0,22 кВ З ВИКОРИСТАННЯМ ГЕНЕТИЧНИХ АЛГОРИТМІВ - Мірошник , О.О.; Тимчук , С.А. (Інститут електродинаміки НАН України, Київ, 2013)
A method of solving the problem of uniform distribution of loads between the phases in the network 0.38 / 0.22 kV is offered. A modified genetic algorithm is used, whose objective functions are the parameter of unevenness load in the network and the number of reconnecting consumers. The operation of separation and adjusting of the set of elitist individuals (Pareto), which is integrated into the genetic algorithm, is implemented by method of pairwise comparisons of alternatives. The original operation of population`s ranking based on introduction of individual`s age allows you automatically to customize the algorithm on the computer's capabilities. On a concrete example a calculation of network is performed and the Pareto set is obtained. The optimum variant of the Pareto set on uniform load distribution between the phases in the network 0.38 / 0.22 kV is chosen. The кeliability of obtained results is tested with the software product Multisim. References 5, tables 2, figures 2.